Transformasi Pendidikan Madrasah melalui Analisis Implementasi Kebijakan Kurikulum Berbasis Cinta - Awza Fhatarani Aulia; Winengan winengan; Hadi Kusuma Ningrat (Mataram University, 2026)
The transformation of madrasa education has become an important part of addressing the challenges of modern education, which are characterized by moral crises, low social empathy, and the dominance of cognitive-oriented learning. This study aims to analyze the implementation of the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) policy as an effort to transform madrasa education toward a more humanistic, religious, and character-oriented learning process for students. The research employed a qualitative approach using a library research method. Data were collected from scientific journals, policy documents, books, and previous studies relevant to the implementation of the Love-Based Curriculum in madrasas. The findings reveal that the implementation of KBC has transformed the learning culture in madrasas through the strengthening of values such as compassion, empathy, tolerance, religious moderation, and reflective learning. The curriculum also shifts the educational paradigm from teacher-centered learning to a more humanistic student-centered approach. However, the implementation of the policy still faces several challenges, including limited teacher competence, insufficient training, and difficulties in evaluating students’ affective achievements. Therefore, synergy among the government, madrasas, teachers, and the community is needed to support the sustainable implementation of the Love-Based Curriculum policy.